Local Cultural Governance and the Ngalaksa Tradition in Rancakalong - Irma Hermayanty; Lalas Sulastri (Department of Public Administration, 2026)
This study analyzes local cultural governance in the preservation of the Ngalaksa Tradition in Rancakalong District, Sumedang Regency, within the framework of regional autonomy. Ngalaksa, a harvest thanksgiving ritual rooted in local wisdom, continues to be practiced annually, yet its sustainability faces modernization pressures and limited integration into formal local policy instruments. Using a descriptive qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis involving customary leaders, village officials, district government representatives, cultural practitioners, and youth. Data were analyzed using Dwiyanto’s (2006) governance dimensions—participation, transparency, accountability, effectiveness, efficiency, and responsiveness—supported by the interactive model of Miles, Huberman, and Saldaña (2019). The findings show that Ngalaksa governance is predominantly driven by customary community actors. Participation is high, and the tradition is effective in strengthening social solidarity and intergenerational learning, while efficiency is supported by gotong royong and voluntary resource mobilization. However, transparency and accountability remain informal due to limited documentation and reporting, and government responsiveness is largely symbolic, with minimal budget allocation and weak incorporation into village planning (APBDes) and the district mid-term development plan (RPJMD). This study recommends strengthening collaborative cultural governance through formal planning integration, adaptive documentation, and sustained policy support to ensure cultural continuity without undermining authenticity. The novelty lies in applying a public governance framework to local cultural preservation under regional autonomy and proposing an adaptive governance model grounded in local wisdom.